Development of WEB Based Police Member Proficiency Test Application - Putra Satria Harahap; Rahma Dewi; Nurkadri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this research is to produce a web-based application for the aptitude test for members of the Indonesian National Police. The type of research used in this research is development research with Research & Development (R&D) research design from Borg and Gall. This research was conducted with 9 research stages namely, (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision. The population in this study used sports science faculty students. The sampling technique used purposive sampling with a Phase I trial of 15 members of the Indonesian National Police Batch 2020/2021 and a Phase II trial with a total of 30 members of the Indonesian National Police Batch 2021/2022. Furthermore, from the Phase I trial with a total of 15 students showing a score of 78.33% with the Eligible criteria, then from the Phase II trial with a total of 30 students showing a score of 93.77% with the Very Eligible category. On the basis of the data obtained, the development of a web-based aptitude test application for police officers was declared feasible to be developed as a web-based aptitude test application for police officers.